Patriotic Leadership and National Development: A Comparative Analysis of The United States and Nigeria - Insights and Lessons - Ita, Victor E. (UUM Press, 2025)
Patriotic leadership is integral to a country’s development and is desirous for effective state-society interactions. Such leadership is often characterized by selflessness, legitimacy, dedication to service, and efficient administration of resources, both human and natural. This paper examines the import of patriotic leadership to national development in the America and Nigeria’s context. The paper employs a historical and descriptive investigative approach with an element of comparative design. It utilizes relevant data collected from documentary sources, which were analysed qualitatively within the framework of Lucian Pye’s modernization theory. From the analysis, it became obvious that America’s history abounds with leaders who, in their private and public lives, have worked assiduously to attain national unity, liberty, equality, and civic rights, hence facilitating national development. In contrast, Nigeria lacks patriotic leaders instilled with vision and commitment to genuine national development. Besides, patriotism and commitment to leadership are ingrained in American culture, which are conducive to national development. In contrast, Nigeria has yet to reach such heights in its political history, with leaders often prioritizing ethnic and regional interests over national interests antagonistic to national development. Consequently, the paper recommends, among others, that for Nigeria to match up with its America counterpart, its political leadership class must undergo a total attitudinal reorientation to embrace national interest and commitment to patriotism and national consciousness. The study offers valuable insights for improving political leadership in Nigeria, emphasizing the need for a nationalistic leadership approach to foster development